CHANGING PLACE: LOCAL PEOPLE, RECREATION AND PROTECTED AREAS ON THE SOUTH COAST OF WESTERN AUSTRALIA1 - Buckley, Amma (The journal of contemporary issues in business and government, 2008)
The environmental impact of local people recreating in nature is an under-studied aspect of protected area management. A recent review of nature-based recreation was undertaken in regional south-western Australia. Surrounded by an array of protected areas, including a national park with World Heritage status, the local residents of this remote West Australian location have relatively unrestricted access to a variety of conserved landscapes. A mineral resources boom in Western Australia has witnessed a return to mining in the area, accompanied by a considerable population increase of both itinerant and permanent miners. For local people and environmental managers alike, this influx has raised concerns about the carrying capacity of this fragile ecosystem to sustain the wilderness recreation activities of the newly arrived mining community. This paper draws on evidence gathered from a recent study and outlines the extent to which local people can be considered visitors to these protected places.